2022
DOI: 10.1080/10790268.2022.2129170
|View full text |Cite
|
Sign up to set email alerts
|

Social disconnectedness and perceived social isolation in persons with spinal cord injury/dysfunction living in the community: A scoping review

Abstract: Structured summary 2Provide a structured summary that includes (as applicable): background, objectives, eligibility criteria, sources of evidence, charting methods, results, and conclusions that relate to the review questions and objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 73 publications
1
10
0
Order By: Relevance
“…Our findings reveal geriatric cancer rehabilitation participation significantly buffered declines in social well-being and familial interactions compared to standard care older cancer cohorts based on the FACT-G social domain. This protective effect against social isolation aligns with previous rehabilitation research demonstrating benefits for loneliness, community participation, and patient-reported social fitness [46]. The social well-being advantages probably arise through counseling and skills building to promote safe, sustainable social connections along with occupational therapy facilitating community mobility [47].…”
Section: Discussionsupporting
confidence: 81%
“…Our findings reveal geriatric cancer rehabilitation participation significantly buffered declines in social well-being and familial interactions compared to standard care older cancer cohorts based on the FACT-G social domain. This protective effect against social isolation aligns with previous rehabilitation research demonstrating benefits for loneliness, community participation, and patient-reported social fitness [46]. The social well-being advantages probably arise through counseling and skills building to promote safe, sustainable social connections along with occupational therapy facilitating community mobility [47].…”
Section: Discussionsupporting
confidence: 81%
“…The participants spoke about how social interaction, both in the form of social support, especially in caregiving, and social participation was imperative and valuable in their recovery after being discharged. Social support has been considered in research as an important outcome in determining recovery of trauma patients (73)(74)(75). It can be in the form of physical care, financial aid, or emotional relief (76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Perceived social isolation, often used interchangeably with loneliness, is a similar subjective measure that also includes feeling like a stranger to others, barely known, avoided, detached from others, and isolated even when not alone (Cimino et al, 2023; PROMIS-SI, 2021; Santini et al, 2020). Social isolation (sometimes referred to as social disconnectedness) is an objective state of having lack of (or limited) social contact and is assessed through measures such as, small social network size, infrequent contact with others, and living alone (Cimino et al, 2023; National Academies of Sciences, Engineering, and Medicine [NASEM], 2020; Santini et al, 2020). It is worth noting that an individual may be surrounded by people and have many social contacts but still experience loneliness, whereas objective social isolation, which reflects actual time alone or without social company may not elicit feelings of loneliness.…”
mentioning
confidence: 99%
“…It focuses on the collective impact of loneliness and social isolation and emphasizes the need for efforts to reduce negative health consequences impacted by loneliness and social isolation. Many individuals with SCI/D experience loneliness and social isolation, and growing evidence suggests that this puts them at increased risk for health consequences (Cimino et al, 2023); this emphasizes the need for efforts to reduce loneliness/isolation in this population. Patients offer unique and important perspectives about their own needs and what they think will be most helpful to improve their outcomes (Bombard et al, 2018).…”
mentioning
confidence: 99%